2010
DOI: 10.1097/wnf.0b013e3181e204e0
|View full text |Cite
|
Sign up to set email alerts
|

Salivary Flow Rate in Patients With Schizophrenia on Clozapine

Abstract: There was a significant increase in salivary flow rate from baseline after starting clozapine, with a significant increase from the second to the third week followed by a "plateau."

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
19
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 9 publications
1
19
0
Order By: Relevance
“…Despite drooling in the groups of schizophrenic patients on clozapine in the studies of Ben‐Aryeh et al (1996) and Rabinowitz et al (1996), the mean salivary flow rate at rest was not different from that of controls. However, in the longitudinal study of Praharaj et al (2010), the salivary flow rate at rest was higher 2–3 weeks after the start of clozapine treatment than before. In the literature, many times the words sialorrhea and drooling are interchangeable used but strictly sialorrhea refers to an increase in saliva production, whereas drooling refers to involuntary spilling of saliva from the mouth (Laskawi and Ellies, 2011).…”
Section: Introductionmentioning
confidence: 77%
“…Despite drooling in the groups of schizophrenic patients on clozapine in the studies of Ben‐Aryeh et al (1996) and Rabinowitz et al (1996), the mean salivary flow rate at rest was not different from that of controls. However, in the longitudinal study of Praharaj et al (2010), the salivary flow rate at rest was higher 2–3 weeks after the start of clozapine treatment than before. In the literature, many times the words sialorrhea and drooling are interchangeable used but strictly sialorrhea refers to an increase in saliva production, whereas drooling refers to involuntary spilling of saliva from the mouth (Laskawi and Ellies, 2011).…”
Section: Introductionmentioning
confidence: 77%
“…Preclinical studies may offer an explanation for the ‘clozapine‐induced sialorrhea’ that occurs in about one‐third of patients under treatment for schizophrenia, a phenomenon that may be particularly troublesome during the night, with choking sensations and the aspiration of saliva (Praharaj et al , 2006, 2010; Gardner and Teehan, 2011). Experiments, using the rat as an animal model, show that clozapine, and its metabolite N ‐desmethylclozapine, exerts dual and opposite actions on the salivation (Ekström et al , 2010a,b; Godoy et al , 2011): a direct excitatory action on muscarinic acetylcholine receptors of the M1 type evokes a low‐grade continuous flow of saliva from the parotid and submandibular glands, and a direct, and marked, inhibitory action on the parasympathetically and sympathetically nerve‐evoked secretion by muscarinic acetylcholine receptors of the M3 type and by α 1 ‐adrenergic receptors.…”
Section: Introductionmentioning
confidence: 99%
“…The strategies suggested to abolish clozapine‐induced sialorrhoea include treatment with amisulpride, a substitute benzamide derivate (3, 4). Data from clinical studies which have measured the volume of saliva secreted, are few and contradictory (5–7). In fact, some authors relate the reported salivation associated with clozapine to a weakened swallowing reflex (8, 9).…”
mentioning
confidence: 99%